Pharmacokinetics of Transdermal Flunixin Meglumine Following a Single Dose in Marine Toads (Rhinella marina) - Gregory Scott; Meghan M. Louis; Julie A. Balko; Claire M. Bublitz; Brigid V. Troan; Ronald E. Baynes; Dustin Smith; Larry J. Minter (Veterinary Medicine International)
Transdermal administration is an important method of pharmacologic drug therapy in amphibians, made possible by their unique skin physiology and permeability. Despite this, there are relatively few studies that investigate transdermal pharmacokinetics in amphibians. The objective of this study was to investigate the pharmacokinetics of transdermal flunixin meglumine applied topically to marine toads (Rhinella marina). Twenty-one adult marine toads were administered flunixin meglumine (3.3 mg/kg) topically on their dorsum and randomized (n = 7/group) to blood collection at two timepoints from the following: 1, 2, 4, 8, 12, and 24 hours (h), using a sparse sampling protocol. Plasma was analyzed by ultra-performance liquid chromatography-tandem mass spectrometry. Samples were analyzed individually and reported as a mean of the samples at each timepoint. The mean peak plasma concentration was 6.31 µg/ml, area under the curve was 29.37 μg-h/mL, and elimination half-life was 2.79 h. No adverse effects were noted in any animals. A subset of 12 animals were euthanized at serial timepoints and necropsied. Histopathology of skin and major organs revealed one minimal superficial lesion in a single toad potentially attributable to flunixin meglumine administration; otherwise, no other treatment-related lesions were observed in 11 of 12 toads. A single topical dose of transdermal flunixin meglumine was rapidly absorbed in marine toads in the current study, and peak plasma concentrations exceeded therapeutic ranges established in cattle with no significant pathologic findings.